Report from Sundance 1999: Religion in Independent Film (The journal of religion and film, 1999)
The following essay is a report on eleven of the movies recently shown at the Sundance Film Festival. Each of these movies is related in one way or another to religion or to one of the many religious themes found frequently in film. Many of these movies will not be widely distributed and those interested in religion and film might never know about them. The main reason for my trip to Sundance, and this essay, is to bring to the attention of our JR & F readers some of the independent movies that might otherwise escape their attention. I have put information on possible distributors and release dates for some of these films at the end of the essay.